Stress and Related Factors among Professional Nurses Working in the Princess Mother National Institute on Drug Abuse Treatment - Duangsoithong, Thiti; Chawanakrasaesin, Kachornwan (Journal of Health Science of Thailand, 2017)
The objective of this study was to assess the level of stress among professional nurses working in drug abuse treatment at the Princess Mother National Institute on Drug Abuse Treatment, Thailand. It was conducted as a cross-sectional survey on stress and related factors during the period from 1 - 31 March 2013. There were 112 nurses enrolled in the study. The data collection tools were comprised of recorded forms and questionnaires which had 2 components: (1) personal profile and type of work, and (2) the causes of stress in a nurse work, together with the stress test developed by Suanprung Hospital, Department of Mental Health. The data were analyzed using percentage, mean and standard deviation as well as the chi-square test to measure the association between stress and the factors relating to the nurses’ working conditions. It was found that the majority (45.5%) of the nurses had stress at a moderate level. The stress was found to be associated with interpersonal relationship in the work (p<0.05); while no significant assocaition was observed between stress and types of work, working atmosphere or management structure. Similar studies in other groups of personnel were recommended in order to reduce stress and further improve the quality of the services in the Institute.